Techno‐Economic Analysis of Methane Pyrolysis in Molten Metals: Decarbonizing Natural Gas - Parkinson, Brett; Matthews, Joshua W.; McConnaughy, Thomas B.; Upham, D. Chester; McFarland, Eric W. (Chemical engineering & technology, 2017)
Methane pyrolysis using a molten metal process to produce hydrogen is compared to steam methane reforming (SMR) for the industrial production of hydrogen. Capital and operating cost models for pyrolysis and SMR were used to generate cash‐flow and production costs for several different molten pyrolysis systems. The economics were most sensitive to the methane conversion and the value obtained for the solid carbon by‐product. The pyrolysis system at 1500 °C is competitive with a carbon tax of $78 t−1; however, if a catalytic process at 1000 °C were developed using a conventional fired heater, it would be competitive with SMR without a carbon dioxide cost penalty. Several pyrolysis alternatives become competitive with increasing carbon dioxide taxes. Methane pyrolysis using a molten metal‐based process to produce carbon and hydrogen is compared to steam methane reforming for the industrial production of hydrogen. Capital and operating cost models for pyrolysis and steam methane reforming were applied to generate cash‐flow and production costs for several different pyrolysis systems making use of molten metals.